2019
DOI: 10.1080/21505594.2019.1614382
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic species of Aspergillus section Terrei display essential physiological features to cause infection and are similar in their virulence potential in Galleria mellonella

Abstract: Aspergillus species account for the majority of invasive mold infections in immunocompromised patients. Most commonly, members of the Aspergillus section Fumigati are isolated from clinical material, followed by isolates belonging to section Terrei. The section Terrei contains 16 accepted species. Six species were found to be of clinical relevance and studied for differences in growth adaptability and virulence potential. Therefore, a set of 73 isolates (22 A. terreus s.s., 8 A. alabamensis, 27 A. citrinoterre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 60 publications
0
16
0
1
Order By: Relevance
“…neoafricanus ) ( Zoran et al. 2018 , Lackner et al. 2019 ).…”
Section: Taxonomy and Prevalence Of Clinically Important Aspergillus Speciesunclassified
“…neoafricanus ) ( Zoran et al. 2018 , Lackner et al. 2019 ).…”
Section: Taxonomy and Prevalence Of Clinically Important Aspergillus Speciesunclassified
“…The production of aleurioconidia by A. terreus s.s., A. carneus, A. flavipes, and A. niveus seems to be a unique feature among the Aspergillus species. These morphologically distinct lateral conidia (aleurioconidia) are attached directly to hyphae and their function is as yet unknown [28].…”
Section: Aspergillusmentioning
confidence: 99%
“…Therefore, our results suggest that urease‐positive strains present in certain proportion in the population of the fungus, and represent natural variation of T rubrum sensu stricto , not an independent entity. Lackner et al 65 obtained comparable results, studying virulence potential of closely related Aspergillus species from the section Terrei . They concluded that virulence is a strain‐specific rather than species‐specific feature.…”
Section: Discussionmentioning
confidence: 77%